Response and Heritability of Oil Palm Type of Seedling K++ and K— to KCl Fertilizer Application in Pre Nursery - irvan maulana amry; Lollie Agustina P. Putri; Diana Sofia Hanafiah (Universitas Sumatera Utara, 2019)
The aims of research was to study the response and heritability of oil palm type of seedling K++ and K– to KCl fertilizer application in pre nursery. This research was conducted at PT. Socfindo Bangun Bandar, Martebing Village, Dolok Masihul District, Serdang Bedagai Regency, Province of North Sumatera, with an altitude of ±60 meters above sea level, starting from February 2017 until May 2017 using Randomized Block Design with 2 factors of treatment: seed type (K++ and K–) and aplication of KCl fertilizer (0 g, 0.15 g and 0.30 g)/seedlings. The data obtained were analyzed using a verbal examination and continued by Duncan's multiple-range test. The parameters observed were plant height, stem diameter, number of leaves, the element of potassium nutrients on the soil and the element of potassium nutrient in the leaves. The results showed that the seed type treatment was significantly different from the plant height, leaf number, and stem diameter. The treatment of KCl fertilizer dose did not significantly affect all parameters. The interaction between the two treatments did not significantly affect all parameters. Parameter of plant height, leaf number and stem diameter showed high heritability value.